Analisis Kegagalan Tata Kelola Investasi Asuransi PT Jiwasraya dalam Perspektif Hukum Ekonomi - Purnomo, Septu; Luthfi Reviana, Salsabilla (Adagium: Jurnal Ilmiah Hukum, 2026)
This research seeks to examine the shortcomings in insurance investment governance at PT Jiwasraya from the viewpoint of economic law. The case involves a series of notable irregularities and breaches. As a result, the study centers on uncovering the repercussions stemming from PT Jiwasraya's mismanagement of insurance investments, as well as identifying the relevant laws and provisions associated with the incident. The methodology applied is the Normative Juridical Research Method, employing both a case-approach and a statute-approach.. This research successfully identifies various instances of deviations and misconduct committed by PT Jiwasraya in its insurance investment governance, alongside the applicable statutory regulations and relevant articles concerning the case.